Monitoring and verification of the feasibility of using water from urban reservoirs located in the city of Caraúbas-RN - Marina Rodrigues Bezerra; João Luiz Gurgel Mota Araújo; João Ítalo da Silva Cunha; Moisés Medeiros de Lima; Daniel Freitas Freire Martins (The Journal of Engineering and Exact Sciences)
The present study aimed to investigate the influence of spatial and temporal variation on the physicochemical characteristics of water in three urban reservoirs in the city of Caraúbas-RN: Saboia Reservoir, Grande Reservoir, and Santa Bárbara Reservoir. This study can provide relevant information about the quality of these water resources and support actions and policies for the conservation and sustainable use of urban water, both for human consumption and irrigation purposes. The analyses and methods adopted followed the guidelines established in the Standard Methods of APHA. The results show that the physicochemical quality of the analyzed waters is directly affected by spatial and temporal variability, with particular emphasis on conductivity, salinity, chloride, and turbidity. Despite the observed influence, most of the parameters fall within the limits established by current legislation, indicating the possibility of using the water for human consumption and irrigation in accordance with these parameters. However, for a comprehensive and accurate assessment of usability, additional analyses encompassing other physicochemical and microbiological parameters would be required.